King Jesus of Nazareth: An Evidential Inquiry - Joshua Sijuwade (Religions, 2025)
This article examines the ‘King Jesus Gospel’ concept proposed by Matthew Bates and Scott McKnight, which frames the biblical gospel as a proclamation of Jesus’ kingship. It addresses the ‘Failure Objection’ that Jesus was merely a failed apocalyptic prophet who died without fulfilling his predictions. Drawing on N.T. Wright’s work, this article constructs the ‘King Jesus Hypothesis’ and evaluates it using evidence from religious transformation, cultural values, and human progress. Employing the Criterion of Predictive Power, it argues that historical religious innovations (drawing on the work of Larry Hurtado), Western moral values (drawing on the work of Tom Holland), and measurable human flourishing (drawing on the work of Steven Pinker) are best explained by Jesus successfully inaugurating God’s Kingdom through cultural transformation rather than apocalyptic intervention. Through this analysis, the article demonstrates that compelling evidence supports Jesus’ kingship despite the Failure Objection.